A novel composite of CdS nanorods growing on a polyaniline-Cd2+ particles surface with excellent formaldehyde gas sensing properties at low temperature. Issue 54 (31st August 2018) - Zhang, Ling; Li, Xifeng; Mu, Zonggang; Miao, Jing; Wang, Kun; Zhang, Rui; Chen, Shunquan
Abstract : A novel composite, CdS nanorods growing on a polyaniline-Cd 2+ particles surface (CdS/PANI) with a hexagonal wurtzite structure phase, was prepared using a hydrothermal synthesis method. Abstract : A novel composite, CdS nanorods growing on a polyaniline-Cd 2+ particles surface (CdS/PANI) with a hexagonal wurtzite structure phase, was prepared using a hydrothermal synthesis method. Methods of XRD, SEM, and FTIR were used to analyze the structure and morphology of the compounds. SEM shows that CdS/PANI consists of sea urchin-like nanorods of about 200–500 nm in length and about 50 nm in diameter. Furthermore, the FTIR spectra show that some characteristic peaks of CdS/PANI are much weaker than those of PANI and the corresponding peaks shift to a higher wavenumber. In addition, the IR stretching frequency of the Cd–S bond for CdS/PANI moved from 630 cm −1 to 674 cm −1 . In the gas sensing experiments, the CdS/PANI-based sensor showed an excellent response to low concentration formaldehyde gas in a wide temperature range of 80–140 °C. The highest response of CdS/PANI could reach about 4.8 to 5 ppm formaldehyde gas at 120 °C. The response and recovery times of the sensor based on CdS/PANI were about 25 s and 30 s to 10 ppm formaldehyde gas, respectively.